Pengembangan Sistem Informasi Manajemen Inventaris Barang (Studi pada SMAN 2 Malang) - Purbaning Dharma Shanti Handoyo; Satrio Agung Wicaksono; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SMA Negeri 2 Malang is a high school that was founded in 1988. The school focuses on Appearance, Achievement and Service. In improving services there are several problems that occur. These problems include the management of goods that are still recorded in books, irregular storage of documents and omissions in writing. These problems can hamper the performance of services provided to the school community. Based on these problems it is necessary to explore the need of stakeholder to produce a solution. The solution provided is in the form of an artifact, which is an information system that can solve problems. Making artifacts using the SDLC approach with the Waterfall model which is implemented in the form of a website. The requirements analysis stage obtained 29 system requirements and 1 non-functional system requirements. The design phase uses OOAD (Object Oriented Analysis and Design) obtained by 8 class controllers and 10 class models. The implementation phase uses MVC as a system architecture and yii2 as a framework. And testing the system using validation testing to users for the overall function of the system and obtained 100% valid results. Compatibility testing results in 9% of problems with various web browsers. Testing user acceptance of the system using User Acceptance Testing obtained 100% value that the user accepts the system that has been developed. This research resulted in an inventory of information systems inventory management artifacts of facilities and infrastructure that have functional requirements according to user needs and have been tested to users.